Assessment of changes to screening programmes: why randomisation is important. (30th March 2015) - Bell, Katy J L; Bossuyt, Patrick; Glasziou, Paul; Irwig, Les
Abstract : Screening programmes sometimes need to be adapted as new technologies and treatments become available. Katy Bell and colleagues argue the best way to assess such changes is through randomised trials within the programmes